Human Vδ1+ T Cells in the Immune Response to Plasmodium falciparum Infection - Hviid, Lars; Smith-Togobo, Cecilia; Willcox, Benjamin E. (Frontiers in Immunology, 2019)
Naturally acquired protective immunity to Plasmodium falciparum malaria is mainly antibody-mediated. However, other cells of the innate and adaptive immune system also play important roles. These include so-called unconventional T cells, which express a γδ T cell receptor (TCR) rather than the αβ TCR expressed by the majority of T cells – the conventional T cells. The γδ T cell compartment can be divided into distinct subsets. One expresses a TCR involving Vγ9 and Vδ2, while another major subset uses instead a TCR composed of Vδ1 paired with one of several types of γ chains. The former of these subsets uses a largely semi-invariant TCR repertoire and responds in an innate-like fashion to pyrophosphate antigens generated by various stressed host cells and infectious pathogens, including P. falciparum. In this short review, we focus instead on the Vδ1 subset, which appears to have a more adaptive immunobiology, but which has been much less studied in general and in malaria in particular. We discuss the evidence that Vδ1+ cells do indeed play a role in malaria and speculate on the function and specificity of this cell type, which is increasingly attracting the attention of immunologists.